Anomalies and Normal Variants of the Cerebral Arterial Supply: A Comprehensive Pictorial Review with a Proposed Workflow for Classification and Significance. Issue 1 (25th September 2017) - Hakim, Arsany; Gralla, Jan; Rozeik, Christoph; Mordasini, Pasquale; Leidolt, Lars; Piechowiak, Eike; Ozdoba, Christoph; El‐Koussy, Marwan
ABSTRACT: Cerebral arteries may exhibit a wide range of variation from normal anatomy, which can be incidentally discovered during imaging. Knowledge of such variants is crucial to differentiate them from pathologies, to understand the etiology of certain pathologies directly related to a vascular variant, and to depict the changes in collateral circulation in patients with certain variants. Detection of particular variants may lead to the discovery of other nonvascular or vascular anomalies, especially aneurysms, and may also affect planning of endovascular or neurosurgical interventions. In this review, we summarize the variants and anomalies of cerebral arteries seen on cross‐sectional imaging classified by a morphological approach and categorize their significance from a clinical perspective. This structured review is intended to serve as a guide for daily use in clinical practice.